1996
DOI: 10.1002/hep.510240107
|View full text |Cite
|
Sign up to set email alerts
|

High rate of mutations in the hepatitis B core gene during the immune clearance phase of chronic hepatitis B virus infection

Abstract: rates of changes were found during the immune clearCross-sectional studies reported that hepatitis B core ance of chronic hepatitis B infection. Interferon therapy gene mutations are associated with active liver disease did not induce a higher rate or specific pattern of mutaand responsiveness to interferon therapy. In view of the tions in the hepatitis B core gene. Response to interferon heterogeneity in published sequences, it is not possible therapy in HBeAg positive patients was unrelated to the to tell wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
59
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 27 publications
11
59
0
Order By: Relevance
“…The acquisition of a mutation at position 5 or 60 has been reported using serum samples in several longitudinal studies (2,6,38). It is interesting to ask how the low-secretion variants, such as mutants P5T and L60V, can be secreted into circulation and eventually predominate over the existing WT HBV population in a natural infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The acquisition of a mutation at position 5 or 60 has been reported using serum samples in several longitudinal studies (2,6,38). It is interesting to ask how the low-secretion variants, such as mutants P5T and L60V, can be secreted into circulation and eventually predominate over the existing WT HBV population in a natural infection.…”
Section: Discussionmentioning
confidence: 98%
“…14,15,18,28,29,36). Finally, a very frequent mutation of HBcAg occurs at codon 5, changing a conserved proline (P) to a threonine (T) (1,2,6,11,13,14,18,22,33,38). While the most common mutation found at HBcAg codon 5 is from P to T, other less frequent changes have also been reported, such as proline to serine (S).…”
mentioning
confidence: 99%
“…Mutations in B-and T-cell epitopes are associated with viral persistence, affecting the host immune response (45)(46)(47). The inflammatory activity produced by viral adaptive mechanisms may persist in up to 15% of cases, leading to the development of cirrhosis (48).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…A previous study by Hosono et al (20) suggested that core mutations in HBV accumulated more errors in tumors compared to non-tumors. The aa 120-140 in the core region exposed on the surface of mature HBeAg and HBcAg are related to the recognition of helper T cells (49)(50)(51) and the immunodominant B-cell recognition sites within the HBcAg have also been found around residues 126-135 (45,46). One of the frequent core mutations is at aa 130, predominated by Thr130 [67 out of 96 (70%)].…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…HBV variants are often found in chronically infected patients (19,37). The most common naturally occurring mutation in human HBV core protein is at amino acid (aa) 97, changing a highly conserved isoleucine (HBsAg subtype adr) or phenylalanine (HBsAg subtype ayw) to a leucine (L) (3,(12)(13)(14)(15)20). In contrast to the established dogma of preferential virion secretion of mature genome for wild-type (WT) hepadnaviruses (17,33,40,44,47,48), the 97L mutation results in secretion of virions containing an immature genome into the medium and is characterized by excessive amounts of minus-strand DNA (47, 48).…”
Section: Hepatitis B Virus (Hbv) Is a Major Human Pathogenmentioning
confidence: 99%